2011
DOI: 10.1016/s1995-7645(11)60059-x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of bacterial vaginosis and its risk factors in HIV/AIDS patients with abnormal vaginal discharge

Abstract: There was a significant statistical difference in prevalence of bacterial vaginosis between the HIV/AIDS group and non-HIV(control) group of patients in the study. Risk behaviors that promote the incidence of bacterial vaginosis should be especially paid attention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…6 In women with trichomoniasis, there is a risk of co-infection with BV. 70 A study conducted by Abbai et al (2016) in South African women showed a significant association between baseline BV infections and incident T. vaginalis infections. 71 Cervical cancer is the most common cause of cancer-related deaths in young women from sub-Saharan Africa.…”
Section: Africamentioning
confidence: 99%
“…6 In women with trichomoniasis, there is a risk of co-infection with BV. 70 A study conducted by Abbai et al (2016) in South African women showed a significant association between baseline BV infections and incident T. vaginalis infections. 71 Cervical cancer is the most common cause of cancer-related deaths in young women from sub-Saharan Africa.…”
Section: Africamentioning
confidence: 99%
“…The literature review identified 108 articles that associated sexually transmitted infections with HIV‐infected women. Among these articles, 33 were chosen based on the abstract and 9 were excluded owing to the criteria given above, leaving 24 articles in the analysis . The results from these articles on the influence of HIV on the prevalence, course, and treatment of other sexually transmitted infections are synthetized in Table .…”
Section: Literature Summarymentioning
confidence: 99%
“…The prevalence of bacterial vaginosis is 36%–43% and is similar in women infected or uninfected with HIV . Vaginal infections are more frequent in women carrying the virus …”
Section: Literature Summarymentioning
confidence: 99%
“…Both HSV-2 and Chlamydia trachomatis infection increase the number of α4β7+ CD4+ T cells in the genital tissue [ 7 , 30 , 42 ]. Bacterial vaginosis, a common syndrome characterised by a shift in vaginal flora composition [ 43 ], has been identified as a specific risk factor for HIV acquisition, also influencing genital tract cytokine concentrations [ 40 , 44 , 45 ]. In this study, we found that BV diagnosis at the time of HIV infection was associated with T/F viruses that had high α4β7 dependence for replication, but found no such associations with STI’s.…”
Section: Discussionmentioning
confidence: 99%